Rethinking status 1A criteria in pediatric cardiac transplantation: A case for the prioritization of patients with single ventricle anatomy supported by ventricular assist devices - Berry, Anna E.; Bearl, David W. (Frontiers in Pediatrics, 2023)
Over the past two years advancements in the techniques and technology of pediatric heart transplantation have exponentially increased. However, even as the number of pediatric donor hearts has grown, demand for this limited resource continues to far outpace supply. Thus, lifesaving support in the form of ventricular assist devices (VAD) has become increasingly utilized in bridging pediatric patients to cardiac transplant. In the current pediatric heart transplant listing criteria, adopted by the United Network for Organ Sharing (UNOS) in 2016, all pediatric patients with a VAD are granted 1A status and assigned top transplant priority regardless of their underlying pathology. However, should this be the case? We suggest that the presence of a VAD alone may not be sufficient for status 1A listing. In doing so, we specifically highlight the heightened acuity, resource utilization, risk profile, and diminished outcomes in patients with single ventricle physiology supported with VAD as compared to patients with structurally normal hearts who would both be listed under 1A status. Given this, from a distributive justice perspective, we further suggest that the lack of granularity in current pediatric cardiac transplant listing categories may inadvertently lead to an inequitable distribution of donor organs and hospital resources especially as it pertains to those with single ventricle anatomy on VAD support. We propose revisiting the current listing priorities in light of improved techniques, technology, and recent data to mitigate this phenomenon. By doing this, pediatric patients with single ventricle disease might be more equitably stratified while awaiting heart transplant.